2021
DOI: 10.1016/j.breast.2021.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Optimized tumour infiltrating lymphocyte assessment for triple negative breast cancer prognostics

Abstract: The tumour microenvironment has been shown to be a valuable source of prognostic information for different cancer types. This holds in particular for triple negative breast cancer (TNBC), a breast cancer subtype for which currently no prognostic biomarkers are established. Although different methods to assess tumour infiltrating lymphocytes (TILs) have been published, it remains unclear which method (marker, region) yields the most optimal prognostic information. In addition, to date, no objective TILs assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Some studies have shown that high NLR is significantly correlated with poor prognosis in triple-negative breast cancer (TNBC) but not in luminal A-like, luminal B-like, or HER2-enriched subtypes [ 8 ]. The predictive prognostic value of TILs has been established for TNBC [ 31 ], but whether peripheral blood neutrophils or lymphocytes have similar value in TNBC is not known. Noh et al [ 13 ] found a significant prognostic value of NLR in luminal subtype breast cancer (ER+ or PR+, HER2−), whereas Yao et al [ 16 ] found that NLR has a significant prognostic value regardless of luminal type or TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that high NLR is significantly correlated with poor prognosis in triple-negative breast cancer (TNBC) but not in luminal A-like, luminal B-like, or HER2-enriched subtypes [ 8 ]. The predictive prognostic value of TILs has been established for TNBC [ 31 ], but whether peripheral blood neutrophils or lymphocytes have similar value in TNBC is not known. Noh et al [ 13 ] found a significant prognostic value of NLR in luminal subtype breast cancer (ER+ or PR+, HER2−), whereas Yao et al [ 16 ] found that NLR has a significant prognostic value regardless of luminal type or TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to prior attempts to apply image analysis for computational assessment of sTIL, such as patch- [ 26 ], object- [ 28 , 29 ], or segmentation-based methods [ 27 , 48 ], our study incorporates all parts of the TIL-WG guideline; from discriminating tissue from glass, and excluding necrotic regions and inflammation related to the non-invasive epithelium, such normal glands and DCIS/LCIS. A recent study [ 33 ] investigated several aspects of computational TIL assessment for prognosis in TNBC. To find the optimal compartment (margin, tumor-associated stroma, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of computational TILs have employed patch- or object detection-based approaches [ 26 , 27 , 28 , 29 ] with manual region outlining as part of the pipeline [ 30 ]. Some of these also used multiplexed immunofluorescence (mIF) [ 31 ] or immunohistochemistry (IHC) [ 32 , 33 ] to classify cells as lymphocytes. All existing studies proposing H&E-based algorithms rely on only manual H&E ground truth annotations to train their model even though the manual human limitations have shown inconsistencies in this task [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This said, current development is still limited by the scarcity of publicly annotated TIL‐associated datasets. TIL detection was also attempted on IHC 53,54 and multispectral IHC, 55 facilitating the assessment of in‐tumour immunology. Deep learning has become an indispensable research tool and sheds light on the prognostic implications, 56 immune response pathway, and activated genes 57 in TIL‐rich cancer.…”
Section: Prognosticationmentioning
confidence: 99%